Proses pengelolaan sampah plastik menjadi paving block di Desa Jetis, Kecamatan Kemangkon, Kabupaten Purbalingga - Alifan Nurin Anamti Dieningrum; Muslihudin Muslihudin; Edy Suyanto (Pascasarjana Universitas Jenderal Soedirman, 2020)
The problem of plastics - if left alone, will not rot because they are difficult to decompose and will cause environmental damage, such as flooding and environmental pollution of water and soil. Inorganic waste management can be done in various ways, one of which is through creative ideas, such as in Jetis village, Purbalingga Regency has a way to solve the problem of plastic, which is used as a paving block. This study aims to determine the process of managing plastic waste for paving blocks at “UD. Wong Cilik ”Jetis Village, Kemangkon District, Purbalingga Regency. This study used the descriptive qualitative method. research data as well as in-depth interviews, observation, namely non-participatory observation, and documentation. The research location was conducted in Jetis Village, Kemangkon District, Purbalingga Regency. The technique of taking informants was purposive sampling. The data analysis technique in this study used an interactive analysis model of Milles and Habberman. The result of this research is the beginning of